An Error Analysis of Grammatical Errors in Students’ Descriptive Texts at Universitas Terbuka - Novita Kusumaning Tyas; Ariana Oktavia (Badan Penerbit STIEPARI Press, 2025)
The focus of this research is on identifying grammar errors in students’ descriptions of office spaces.Using Corder’s (1974) taxonomy, four types of errors were identified: omission, addition, misformation, and misordering. Data were collected from eight students and analyzed qualitatively. The results show that misformation was the most frequent error, followed by omission, addition, and misordering. These findings suggest that students’ writing skills are still influenced by incomplete language development and native language interference. The study recommends grammar-focused feedback and the use of authentic materials to improve students’ accuracy and fluency in English writing.